1997
DOI: 10.1002/(sici)1097-0142(19970115)79:2<362::aid-cncr20>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Telomerase activity in bladder carcinoma and its implication for noninvasive diagnosis by detection of exfoliated cancer cells in urine

Abstract: These results suggest that telomerase could be a good diagnostic marker for the early noninvasive identification of patients with bladder carcinoma by facilitating the detection of exfoliated immortal cancer cells in their urine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
82
0
3

Year Published

1997
1997
2005
2005

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 185 publications
(92 citation statements)
references
References 24 publications
7
82
0
3
Order By: Relevance
“…It was shown that, regardless of tumour stage or degree of di erentiation, telomerase activity could be identi®ed in nearly all tissue samples derived from bladder carcinomas (Table 1) but not in normal urothelium. Thus, the fundamental prerequisites for a diagnostic method with high sensitivity and speci®city are ful®lled (Gelmini et al, 2000;Ito et al, 1998a;Kamata et al, 1996;Kinoshita et al, 1997;Kyo et al, 1997;Lancelin et al, 2000;Lee et al, 1998;Lin et al, 1996;Linn et al, 1997;May®eld et al, 1998;MuÈ ller et al, 1996;Rahat et al, 1999;Yokota et al, 1998;Yokota et al, 1998;Yokota et al, , 1996), low levels of telomerase activity were identi®ed in dysplastic urothelium by Lin et al (1996) in one of two cases and by Yoshida et al (1997) in two of two cases. In a very small number of cases, telomerase activity was detected in histologically normal urothelial tissue immediately adjacent to con®rmed tumours.…”
Section: Tissue Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that, regardless of tumour stage or degree of di erentiation, telomerase activity could be identi®ed in nearly all tissue samples derived from bladder carcinomas (Table 1) but not in normal urothelium. Thus, the fundamental prerequisites for a diagnostic method with high sensitivity and speci®city are ful®lled (Gelmini et al, 2000;Ito et al, 1998a;Kamata et al, 1996;Kinoshita et al, 1997;Kyo et al, 1997;Lancelin et al, 2000;Lee et al, 1998;Lin et al, 1996;Linn et al, 1997;May®eld et al, 1998;MuÈ ller et al, 1996;Rahat et al, 1999;Yokota et al, 1998;Yokota et al, 1998;Yokota et al, , 1996), low levels of telomerase activity were identi®ed in dysplastic urothelium by Lin et al (1996) in one of two cases and by Yoshida et al (1997) in two of two cases. In a very small number of cases, telomerase activity was detected in histologically normal urothelial tissue immediately adjacent to con®rmed tumours.…”
Section: Tissue Samplesmentioning
confidence: 99%
“…Sensitivities for urine samples have ranged between 0% and 100% ( Rahat et al, 1999;Ramakumar et al, 1999;Yokota et al, 1998;Yoshida et al, 1997). The reasons for these widely divergent ®ndings remain unclear, particularly because methodical di erences, such as in the treatment of the samples, are not apparent.…”
Section: Urine Samplesmentioning
confidence: 99%
“…Expression of rTERT was evaluated by comparison of the results with those of normal controls at each experimental stage. Telomere length assay To analyze telomere length, we employed southern hybridization for terminal restriction fragments (TRFs) using a (TTAGGG) 4 probe. Genomic DNA was extracted from a mixture of exfoliated urothelial cells from ten rats.…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that 80 to 90% of bladder tumors express telomerase activity, 2) and that the detection of telomerase activity in bladder tumor tissues and/or in exfoliated tumor cells in urine is useful as a new diagnostic tool. 3,4) To examine the critical point at which telomerase activation occurs in the course of bladder carcinogenesis, we measured telomerase activity in bladder epithelium during N-butyl-N-(4-hydroxybutyl)nitrosamine (BBN) carcinogenesis in the rat. BBN bladder carcinogenesis is thought to be a model for superficial bladder tumor.…”
mentioning
confidence: 99%
“…To date, there are no established tumour markers available, although several have been investigated in preliminary studies with promising results in terms of diagnostic or prognostic use. These include bladder-tumour associated analyte (BTA; Sarosdy et al, 1995;D'Hallewin and Baert, 1996;Leyh et al, 1997), nuclear matrix protein 22 (NMP22; Soloway et al, 1996), telomerase activity (Kinoshita et al, 1997;Yoshida et al, 1997), Ki-67 antigen and p53 protein expression (Tsuji et al, 1997), microsatellite analysis (Mao et al, 1996;Steiner et al, 1997) and matrix metalloproteinases, their inhibitors and activators (Gohji et al, 1998;Kanayama et al, 1998).…”
mentioning
confidence: 99%